1997
DOI: 10.1074/jbc.272.50.31755
|View full text |Cite
|
Sign up to set email alerts
|

Signal Transduction-mediated Activation of the Aryl Hydrocarbon Receptor in Rat Hepatoma H4IIE Cells

Abstract: We have investigated mechanisms of omeprazole (OME)-mediated induction of CYP1A1 and CYP3A, using the rat hepatoma H4IIE cell line, in comparison with mechanisms exerted by traditional aryl hydrocarbon receptor (AhR) ligands such as benso(a)pyrene (B(a)P) and 2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD). OME did not bind specifically to AhR, and it could not activate the AhR complex in rat cytosol to a xenobioticresponsive element (XRE)-binding form in vitro. Genistein, a tyrosine kinase inhibitor, and daidzein,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
83
1

Year Published

1998
1998
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 107 publications
(91 citation statements)
references
References 43 publications
7
83
1
Order By: Relevance
“…First, activation of the Ah receptor pathway mediates CYP1A1 induction by omeprazole (Daujat et al, 1992;Backlund et al, 1997;Dzeletovic et al, 1997). Second, dioxinresponsive elements to which the Ah receptor/Arnt heterodimer may bind have been identified in the 5Ј-flanking region of human MRP3 (Takada et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…First, activation of the Ah receptor pathway mediates CYP1A1 induction by omeprazole (Daujat et al, 1992;Backlund et al, 1997;Dzeletovic et al, 1997). Second, dioxinresponsive elements to which the Ah receptor/Arnt heterodimer may bind have been identified in the 5Ј-flanking region of human MRP3 (Takada et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…1A for structures) cause induction of the CYP1A1 gene in rat hepatoma H4IIE cells (Backlund et al, 1997(Backlund et al, , 1999Werlinder et al, 2001). In the case of OME, it has been shown that this benzimidazole is not capable of transformation of the AhR, in cytosol from H4IIE cells or mouse Hepa1 cells (Backlund et al, 1997;Dzeletovic et al, 1997).…”
mentioning
confidence: 99%
“…When OME was treated before cytosol isolation, a reduction in 2,3,7,8-tetrachlorodibenzo-p-dioxin binding to AhR was observed in rabbit hepatocytes (Lesca et al, 1995). In the electrophoresis mobility shift assay, OME failed to shift the AhR/Arnt complex signal when it was added to the cytosol isolated from human tumor cells (Daujat et al, 1992;Backlund et al, 1997). In contrast, cytosol from cells pretreated with OME showed a retardation band specific to the AhR/Arnt complex (Quattrochi and Tukey, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, similar to the typical AhR ligands, OME induces AhR/Arnt translocation into the nucleus, which then binds to the XRE sequence required for CYP1A1 induction (Quattrochi and Tukey, 1993;Yoshinari et al, 2008). Several studies reported that OME-mediated AhR activation occurred via a protein tyrosine kinase pathway in both rat and human hepatoma cells (Backlund et al, 1997;Kikuchi et al, 1998;Lemaire et al, 2004;Backlund and Ingelman-Sundberg, 2005). Thus, the molecular mechanisms of OME-mediated AhR activation are not completely understood.…”
Section: Introductionmentioning
confidence: 99%